Unveiling ADHD’s impact on higher education students: statistics anxiety, attitudes, and statistical literacy - Ryder, Chen Hanna; Gal, Carmit; Sarid, Miriam; Klemer, Anat (Frontiers in Psychiatry, 2025)
ObjectiveThis study investigated the relationship between ADHD and statistical literacy in higher education. We examined how ADHD diagnostic status (diagnosed, suspected undiagnosed, and non-ADHD) relates to statistics anxiety, attitudes, and literacy outcomes, thereby illuminating challenges associated with formal diagnosis and support access. Furthermore, we explored the roles of attitudes, anxiety, ADHD status, and academic degree as predictors of statistical literacy.MethodWe compared three groups among 405 higher education students: students with formally diagnosed ADHD (n = 80), those with suspected undiagnosed ADHD (n = 74), and students without ADHD (n = 251).ResultsBoth groups with ADHD reported significantly higher levels of statistics anxiety and less favorable attitudes toward statistics compared to the non-ADHD group. Surprisingly, no significant differences emerged in statistical literacy performance across the three groups. Multiple regression analysis revealed that attitudes toward statistics and academic degree were significant predictors of statistical literacy.ConclusionAlthough students with ADHD experience heightened anxiety and maintain less favorable attitudes toward statistics, they remarkably achieve performance levels comparable to their non-ADHD peers. These findings challenge conventional assumptions about ADHD’s impact on quantitative academic capabilities and highlight the resilience of students with ADHD. The results emphasize the need for targeted interventions focusing on reducing anxiety and improving attitudes while recognizing students’ academic potential.